PENGARUH PELATIHAN TERHADAP PRODUKTIVITAS PELAKU IKM DI KABUPATEN PESISIR SELATAN - Ferdinand, Nabil Ananta; Eriyanti, Fitri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Fishermen are a profession that cannot be relied upon as the sole source of livelihood due to its heavy dependence on natural conditions. Therefore, people working as fishermen are encouraged to seek side professions, such as processing seafood catch into ready-to-eat products. This has led to the formation of IKM (Small and Medium Industries) groups to optimize the potential available. This study aims to examine the effect of training on the productivity of IKM in Koto XI Tarusan District, Pesisir Selatan Regency. The training provided is expected to enhance the skills and knowledge of the community regarding seafood processing, enabling them to innovate creatively and produce high-quality processed products. The sample for this study consisted of 45 fishery IKM actors who have participated in training in Koto XI Tarusan District, Pesisir Selatan Regency. The research method used is a quantitative approach, with data collection through a questionnaire. The results of the study indicate that the training has a significant and positive effect on the productivity of IKM actors in Koto XI Tarusan District, Pesisir Selatan Regency.